MouBeAT: A New and Open Toolbox for Guided Analysis of Behavioral Tests in Mice - Bello-Arroyo, Elísabet; Roque, Hélio; Marcos, Alberto; Orihuel, Javier; Higuera-Matas, Alejandro; Desco, Manuel; Caiolfa, Valeria R.; Ambrosio, Emilio; Lara-Pezzi, Enrique; Gómez-Gaviro, María Victoria (Frontiers in Behavioral Neuroscience, 2018)
Animal behavioral tests are essential to understand the bases of neurologic and psychological disorders, which can be evaluated by different methodological and experimental models. However, the quantification of behavioral tests results is limited by the considerable amount of time needed for manual evaluation and the high costs of automated analysis software. To overcome these limitations, we describe here a new, open source toolbox for ImageJ, called MouBeAT (Mouse Behavioral Analysis Toolbox), designed to analyze different behavioral tests in rodents semi-automatically. These tests include Open Field (OF), Elevated Plus Maze (EPM), Y-maze test (YM) and Morris Water Maze (MWM). MouBeAT showed a very high correlation with manual evaluation in all the parameters analyzed for all the behavioral tests, reinforcing its value as an accurate analysis tool. This new tool is freely available online.